Modeling and Control Analysis of Wind Turbine of Two Bladed and Three Bladed Wind Turbine Systems - L V Suresh Kumar; Chintu Jaganmohanarao; Sai Lakshmi B (Institute of Advanced Engineering and Science, 2015)
The wind power industry is currently the fastest growing renewable energy sector throughout the world. the aim of this paper is to implement the mathematical model and simulations torque control of two bladed and three bladed wind turbine systems by changing power coefficient, tip speed ratio and pitch angle values for different wind speeds.To ensure an economically competitive wind power production, the trend is to increase the turbine size while at the same time minimize material usage. In this paper we have two cases are developed one for two bladed and another for the three bladed wind turbines and compare the simulation results of both cases. The two balade and three blade systems are mathmatically developed and implemented in matlab simulink.